Efeito antirreabsortivo ósseo alveolar do ranelato de estrôncio via redução de TNF-α e IL-1β na periodontite induzida por ligadura em ratos - Ribeiro, Rafael Reis (2017)
Periodontitis is an inflammatory disease characterized by dysbiosis and alveolar bone resorption (ABR). Strontium ranelate (SrR), a drug used to treat osteoporosis, has been notable for its bone anabolic and antiresorptive effects. The anti-inflammatory and antiresorptive effects of SrR on ligature-induced alveolar bone resorption were evaluated. For this, female Wistar rats (170±20 g; n= 6/group), submitted to 28 days of ligature (3/0 nylon thread) of the second upper molars, received per os daily water for injection (vehicle) or SrR (70, 210 and 630 mg/kg). After euthanasia, its jaws were removed, and the ABR was analyzed by macroscopy, microscopy and immunohistochemistry for TNF-α, IL-1β, RANKL, OPG and TRAP. Neutrophil influx was analyzed by myeloperoxidase (MPO) activity in the gingiva. Systemicaly, it were evaluated: serum levels of bone-specific alkaline phosphatase (BALP) and AST and ALT transaminases, hepatic index, leukogram and animal weight. Ligature for 28 days significantly increased ABR, as seen by macroscopy and microscopy, and MPO, as well as immunostaining for TNF-α, IL-1β, RANKL and TRAP, increased the RANKL/OPG ratio, reduced BALP, caused leukocytosis, and weight reduction in the first days after ligature, without liver changes. SrR (210 and 630 mg/kg) significantly reduced ABR by 22% and 45%, respectively, as well (SrR 630 mg/kg) reduced the furcation lesion by 64% compared to the vehicle group. Histology showed significant reduction of leukocyte infiltrate and bone and cement resorption [vehicle: Md=2 (2-2), Mg=1 (1-1)], as well as of the immunostaining for TNF-α, IL-1β, RANKL and TRAP by 51%, 54%, 63% and 66%, respectively, and of the RANKL/OPG ratio, without change of MPO. In addition, SrR (630 mg/kg) prevented the reduction of BALP (60%, p=0.01), reduced leukocytosis, and did not alter transaminases and the time course of animal weight variation. In summary, SrR presented bone antiresorptive effect by both reduction of inflammatory response and support bone anabolism, without systemic alterations in animals.